2011
DOI: 10.1118/1.3660328
|View full text |Cite
|
Sign up to set email alerts
|

Effects of motion, attenuation, and scatter corrections on gated cardiac SPECT reconstruction

Abstract: Purpose: In gated cardiac single photon emission computed tomography (SPECT), image reconstruction is often hampered by various degrading factors including depth-dependent spatial blurring, attenuation, scatter, motion blurring, and low data counts. Consequently, there has been significant development in image reconstruction methods for improving the quality of reconstructed images. The goal of this work is to investigate how these degrading factors will impact the reconstructed myocardium when different recon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 16 publications
2
33
0
Order By: Relevance
“…The FBP without AC plus lowpass filtering is currently the standard as per ASNC guidelines, 32 while the additional temporal filtering is the standard employed clinically at UMass Medical School. 22,23 This method is referred to as "ST121. "…”
Section: Iid1 Clinical Spatiotemporal Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The FBP without AC plus lowpass filtering is currently the standard as per ASNC guidelines, 32 while the additional temporal filtering is the standard employed clinically at UMass Medical School. 22,23 This method is referred to as "ST121. "…”
Section: Iid1 Clinical Spatiotemporal Methodsmentioning
confidence: 99%
“…In recent years, 4D reconstruction methods that exploit the temporal correlation among the gated frames have been developed to improve image quality in GSPECT, aiming to achieve better perfusion defect detectability and functional assessment. [17][18][19][20][21][22][23] Indeed, in our recent work, 23 it was demonstrated that use of temporal processing in GSPECT reconstruction can have greater impact on the accuracy of the myocardium than correction of other degrading factors. However, all these 4D studies were conducted at the standard dose level with the focus on image quality improvement.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most software packages simultaneously display a cinematic playback of the original rotating data during this data processing step, if data were acquired by a rotating gamma camera, and users need to inspect this cine for issues that can affect data integrity, such as patient vertical and twisting motion. 8 Even cooperative patients may be unable to control their motion, such as due to coughing or neurologic motor disorders, so that it is always important to verify the data are not compromised by patient motion, or to use post-acquisition motion correction software that can be used manipulate the vertical position of projection data. 9 Currently, efforts are underway to enable users to correct gated SPECT MPI reconstructions simultaneously for both pulmonary and cardiac motion.…”
mentioning
confidence: 99%